Complex functions and inner product $\langle \frac{\partial f}{\partial z} , g\rangle $
I'm working through this academic paper: Stability of the Solutions of Differential Equations whose author is Bernard Beauzamy. A link to paper. In the academic paper, it works with the norm \begin{equation*} \left\Vert f\right\Vert= \left( \int_{0}^{\infty}\int_{0}^{2\pi} e^{-r^2} |f(re^{i\theta})|^2 r dr\frac{d\theta}{\pi} \right)^{1/2} \end{equation*} for analytic polynomials and the scalar product associated is \begin{equation*} \langle f,g\rangle= \int_{0}^{\infty}\int_{0}^{2\pi} e^{-r^2}f(re^{i\theta})\overline{g(re^{i\theta})} r dr\frac{d\theta}{\pi} \end{equation*} The lemma that I'm trying to check says the following:
For any $f$, $g$ in $\mathcal{P}_2$ \begin{equation*} \left\langle \frac{\partial f}{\partial z} , g\right\rangle = \langle f, zg \rangle \qquad \langle zf,g \rangle = \left\langle f, \frac{\partial g}{\partial z} \right\rangle \end{equation*} the functions $f$ and $g$ are given by \begin{equation*} f(z) = \sum_{j=0}^{\infty} a_j z^j, \quad g(z) = \sum_{j=0}^{\infty} b_j z^j. \end{equation*} The derivative of $f$ with respect to $z$ is \begin{equation*} \frac{\partial f}{\partial z} = \sum_{j=1}^{\infty} a_j j z^{j-1}. \end{equation*} so the scalar product is \begin{align*} \left\langle \frac{\partial f}{\partial z}, g \right\rangle &= \int_{0}^{\infty} \int_{0}^{2\pi} e^{-r^2} \left(\sum_{j=1}^{\infty} a_j j (re^{i\theta})^{j-1}\right) \overline{\left(\sum_{k=0}^{\infty} b_k (re^{i\theta})^k\right)} r \, dr \, \frac{d\theta}{\pi} \\ &= \int_{0}^{\infty} \int_{0}^{2\pi} e^{-r^2} \sum_{j=1}^{\infty} \sum_{k=0}^{\infty} a_j j r^{j-1} e^{i(j-1)\theta} \overline{b_k} r^k e^{-ik\theta} r \, dr \, \frac{d\theta}{\pi} \\ &= \int_{0}^{\infty} \int_{0}^{2\pi} e^{-r^2} \sum_{j=1}^{\infty} \sum_{k=0}^{\infty} a_j \overline{b_k} j r^{j+k} e^{i(j-k-1)\theta} r \, dr \, \frac{d\theta}{\pi}. \end{align*}
\begin{equation*} \int_{0}^{2\pi} e^{i(j-k-1)\theta} \frac{d\theta}{\pi} = \begin{cases} 1 & \text{if } j = k+1, \\\\ 0 & \text{if } j \neq k+1. \end{cases} \end{equation*}Hence \begin{align*} \left\langle \frac{\partial f}{\partial z}, g \right\rangle &= \int_{0}^{\infty} e^{-r^2} \sum_{k=0}^{\infty} a_{k+1} \overline{b_k} (k+1) r^{2k+3} r \, dr \\ &= \sum_{k=0}^{\infty} a_{k+1} \overline{b_k} (k+1) \int_{0}^{\infty} e^{-r^2} r^{2k+3} dr. \end{align*}
The other scalar product is \begin{align*} \langle f, zg \rangle &= \int_{0}^{\infty} \int_{0}^{2\pi} e^{-r^2} \left(\sum_{j=0}^{\infty} a_j (re^{i\theta})^j\right) \overline{\left(\sum_{k=0}^{\infty} b_k r^{k+1} e^{i(k+1)\theta}\right)} r \, dr \, \frac{d\theta}{\pi} \\ &= \int_{0}^{\infty} \int_{0}^{2\pi} e^{-r^2} \sum_{j=0}^{\infty} \sum_{k=0}^{\infty} a_j \overline{b_k} r^{j+k+1} e^{i(j-k-1)\theta} r \, dr \, \frac{d\theta}{\pi}. \end{align*}
Again, integrating over $\theta$ and $j=k+1$ \begin{align*} \langle f, zg \rangle &= \int_{0}^{\infty} e^{-r^2} \sum_{k=0}^{\infty} a_{k+1} \overline{b_k} r^{2k+3} r \, dr \\ &= \sum_{k=0}^{\infty} a_{k+1} \overline{b_k} \int_{0}^{\infty} e^{-r^2} r^{2k+3} dr. \end{align*}
\begin{align*} \langle \frac{\partial f}{\partial z}, g \rangle &= \sum_{k=0}^{\infty} a_{k+1} \overline{b_k} (k+1) \int_{0}^{\infty} e^{-r^2} r^{2k+3} dr, \\\\ \langle f, zg \rangle &= \sum_{k=0}^{\infty} a_{k+1} \overline{b_k} \int_{0}^{\infty} e^{-r^2} r^{2k+3} dr. \end{align*}These are not equal due to the factor $(k+1)$ present in $\left\langle \frac{\partial f}{\partial z}, g \right\rangle$. So I don't know where the error is.
2 answers
You are accessing this answer with a direct link, so it's being shown above all other answers regardless of its score. You can return to the normal view.
There are multiple issues with how you compute the exponent of $r$.
The first issue is you compute $r^{j-1}r^k = r^{j+k}$ rather than $r^{j+k-1}$.
You compound this error when you substitute $j = k+1$ into $r^{j+k}$ (which should be $r^{j+k-1}$) in the formula for $\left\langle\frac{\partial f}{\partial z},g\right\rangle$. You end up with $r^{2k+3}$ rather than $r^{2k+1}$ (which should actually be $r^{2k}$).
You make the same mistake in the formula for $\langle f,zg\rangle$ where $r^{j+k+1}$ should become $r^{2k+2}$ but you have $r^{2k+3}$. That said, in this case you make another mistake which cancels this out by "multiplying" $r^{2k+3}r$ to just $r^{2k+3}$ instead of $r^{2k+4}$ when you pull the sum out of the integral.
Without these mistakes you would end up with $$\begin{align} \left\langle \frac{\partial f}{\partial z}, g\right\rangle &= \sum_{k=0}^\infty a_{k+1}\overline{b_k} (k+1)\int_0^\infty e^{-r^2}r^{2k+1} dr \\ \langle f, zg \rangle &= \sum_{k=0}^\infty a_{k+1}\overline{b_k} \int_0^\infty e^{-r^2}r^{2k+3} dr \end{align}$$
Applying integration by parts to the integral in the second equation will reduce it to the first, i.e. a $k+1$ factor will pop out and the power of the $r^{2k+3}$ will be reduced by $2$. (This is easiest to see, for me at least, by first doing a $u$-substitution with $u=-r^2$.)
1 comment thread
The first case $\langle \frac{\partial f}{\partial z} , g \rangle$. Change of variable \begin{align*} u =r^2 \ \qquad du =2r dr \end{align*} \begin{align*} (k+1)\int_{0}^{\infty} e^{-r^2}r^{2k+1}dr=\int_{0}^{\infty} e^{-u}u^{k +1/2}\frac{1}{2\sqrt{u}}du = \frac{1}{2}\int_{0}^{\infty}e^{-u}u^{k}du = (k+1)\frac{\Gamma\left((k+1)/1\right)}{2}=(k+1)\frac{\Gamma (k+1)}{2}=\frac{(k+1)!}{2} \end{align*} The second case $\langle f, zg \rangle $. The same change of variables \begin{align*} (k+1)\int_{0}^{\infty} e^{-r^2}r^{2k+3}dr=\int_{0}^{\infty} e^{-u}u^{k +3/2}\frac{1}{2\sqrt{u}}du = \frac{1}{2}\int_{0}^{\infty}e^{-u}u^{k+1}du = \frac{\Gamma\left((k+2)/1\right)}{2}=\frac{\Gamma (k+2)}{2}=\frac{(k+1)!}{2} \end{align*} Hence, the inner products are equals. (In the last equality i used the gauss integral and its relation with Gamma function. Look at in Wikipedia)
2 comment threads